2023
DOI: 10.15173/ijsap.v7i1.5260
|View full text |Cite
|
Sign up to set email alerts
|

Partnering with students to redesign an introductory chemistry laboratory course: An exploration of the process and implications

Abstract: The most effective teaching and learning environments are those in which students are involved as active partners with faculty, and the greatest impact occurs when faculty go beyond asking students for feedback and instead involve them in design, production, and implementation. In this paper, we explore the process of student-faculty co-creation by presenting a specific case involving students as partners in the redesign of an introductory chemistry laboratory course to incorporate more group learning, support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Similarly, a chemistry instructor who worked with several student partners to redesign an introductory chemistry laboratory course asserted that the lessons they learned "were invaluable and not only enhanced this specific course, but their teaching overall" (Jardine et al, 2023).…”
Section: Pedagogical Partnerships Support the Enactment Of Equitable ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a chemistry instructor who worked with several student partners to redesign an introductory chemistry laboratory course asserted that the lessons they learned "were invaluable and not only enhanced this specific course, but their teaching overall" (Jardine et al, 2023).…”
Section: Pedagogical Partnerships Support the Enactment Of Equitable ...mentioning
confidence: 99%
“…Mercer-Mapstone et al ( 2021) also report that students and faculty working together on an academic development project aiming to enhance the inclusivity of science curricula experienced changes in perception, like an increase in sense of belonging for both faculty and students and fairness in decisionmaking for students. Likewise, Jardine et al (2023) report that participation in a course redesign project increased student partners' sense of belonging. And finally, Bunnell et al (2021) explain that: "The experience of co-creating the Being Human in STEM Initiative increased the pioneers' stakes in the Amherst community, providing a thread of continuing connection, belonging, and personal investment" (37).…”
Section: Pedagogical Partnerships Foster a Sense Of Mattering Belongi...mentioning
confidence: 99%
“…Promising examples of doing so encompass students-as-partners approaches, namely, perceiving students as co-creators of their studies. Academic research has started to embed the students-as-partners approach as an initiative for teaching to involve students in the educational design (Jardine et al, 2023). Anderson and colleagues (2023) identified four beneficial themes for students experiencing co-design settings.…”
Section: Chapter In Picturesmentioning
confidence: 99%
“…Beyond that, other case studies have identified further positive outcomes of students-as-partner practices in course design. Students experience positive learning experiences, increased skill and personal development, flexibility, empowerment, and effective communication systems (Georgieva et al, 2023;Jardine et al, 2023;Payne et al, 2023). Furthermore, teachers benefit from directly perceiving students' development (Payne et al, 2023).…”
Section: Chapter In Picturesmentioning
confidence: 99%
See 1 more Smart Citation